Antibacterial Compounds-Macrolactin Alters the Soil Bacterial Community and Abundance of the Gene Encoding PKS - Yuan, Jun; Zhao, Mengli; Li, Rong; Huang, Qiwei; Rensing, Christopher; Raza, Waseem; Shen, Qirong (Frontiers in Microbiology, 2016)
Macrolactin produced by many soil microbes has been shown to be an efficient antibacterial agent against many bacterial pathogens. However, studies examining the effect of macrolactin on both the soil bacterial community and the intrinsic bacterial species that harbor genes responsible for the production of this antibiotic have not been conducted so far. In this study, a mixture of macrolactin was isolated from the liquid culture of Bacillus amyloliquefaciens NJN-6, and applied to the soil once a week for four weeks. 16S rRNA Illumina MiSeq sequencing showed that continuous application of macrolactin reduced the α-diversity of the soil bacterial community and thereby changed the relative abundance of microbes at both the phylum and genus level. The relative abundance of Proteobacteria and Firmicutes was significantly increased along with a significant decrease in the relative abundance of Acidobacteria. However, the application of macrolactins had an insignificant effect on the total numbers of bacteria. Further, the native gene responsible for the production of macrolactin, the gene encoding polyketide synthase (PKS) was reduced in copy number after the application of macrolactin. The results of this study suggested that a bactericide from a microbial source could decrease the diversity of the soil bacterial community and change the bacterial community structure. Moreover, the populations of the intrinsic bacterial species which harbor genes responsible for macrolactin production were inhibited when the external source antibiotic was applied.